Nanoporous Graphene: Facile Fabrication of Large‐Area Atomically Thin Membranes by Direct Synthesis of Graphene with Nanoscale Porosity (Adv. Mater. 49/2018). Issue 49 (3rd December 2018) - Kidambi, Piran R.; Nguyen, Giang D.; Zhang, Sui; Chen, Qu; Kong, Jing; Warner, Jamie; Li, An‐Ping; Karnik, Rohit
Abstract : Facile fabrication of large‐area atomically thin membranes is reported by Piran R. Kidambi, Rohit Karnik, and co‐workers in article number1804977 . A simple reduction in temperature during the synthesis allows direct formation of nanopores in graphene. By solution‐casting a hierarchically porous support on nanoporous graphene, large‐area atomically thin membranes for dialysis applications are demonstrated. The image shows nanoporous graphene transferred on to porous polycarbonate supports (photograph by Felice Frankel).